High-performance extended short-wavelength infrared PBn photodetectors based on InAs/GaSb/AlSb superlattices - Jiang, Junkai; Chang, Faran; Zhou, Wenguang; Li, Nong; Chen, Weiqiang; Jiang, Dongwei; Hao, Hongyue; Wang, Guowei; Wu, Donghai; Xu, Yingqiang; Niu, Zhi-Chuan (Chinese physics B, 2023)
High performance short-wavelength infrared PBn photodetectors based on InAs/GaSb/AlSb superlattices on GaSb substrate have been demonstrated. At 300 K, the device exhibits a 50% cut-off wavelength of ∼ 2.1 μm as predicted from the band structure calculation; the device responsivity peaks at 0.85 A/W, corresponding to a quantum efficiency (QE) of 56% for 2.0 μm-thick absorption region. The dark current density of 1.03 × 10 −3 A/cm 2 is obtained under 50 mV applied bias. The device exhibits a saturated dark current shot noise limited specific detectivity ( D *) of 3.29 × 10 10 cm⋅Hz 1/2 /W (at a peak responsivity of 2.0 μm) under –50 mV applied bias.